The Impact of Genetics and Hormonal Contraceptives on the Steroid Profile in Female Athletes - Schulze, Jenny J.; Mullen, Jenny E.; Berglund Lindgren, Emma; Ericsson, Magnus; Ekström, Lena; Hirschberg, Angelica Lindén (Frontiers in Endocrinology, 2014)
The steroid module of the Athlete Biological Passport (ABP), the newest innovation in doping testing, is currently being finalized for implementation. Several factors, other than doping, can affect the longitudinal steroid profile. In this study we investigated the effect of hormonal contraceptives as well as the effect of three polymorphisms on female steroid profiles in relation to doping controls. The study population consisted of 79 female elite athletes between the ages of 18 to 45. Hormonal contraceptives were used by 32 % of the subjects. A full urinary steroid profile was obtained using World Anti-Doping Agency accredited methods. In addition all subjects were genotyped for copy number variation of UGT2B17 and SNPs in UGT2B7 and CYP17. Subjects using hormonal contraceptives excreted 40 % less epitestosterone as compared to non-users (p = 0.005) but showed no difference in testosterone excretion. When removing individuals homozygous for the deletion in UGT2B17, the testosterone to epitestosterone (T/E) ratio was 29 % higher in the hormonal contraceptives group (p = 0.016). In agreement with previous findings in men, copy number variation of UGT2B17 had significant effect on female urinary testosterone excretion and therefore also the T/E ratio. Subjects homozygous for the T allele of CYP17 showed a lower urinary epitestosterone concentration than the other CYP17 genotypes. It is of great importance that the athlete’s steroidal passport can compensate for all possible normal variability in steroid profiles from women. Therefore, considering the large impact of hormonal contraceptives on female steroid profiles, we suggest that the use of hormonal contraceptives should be a mandatory question on the doping control form.